Peri-lead edema in deep brain stimulation: common complication or rare challenge? - Nevrly, Martin; Blazek, Filip; Krahulik, David; Otruba, Pavel; Cechakova, Eva; Afifi, Ahmed Naser Mohamed; Kanovsky, Petr (Frontiers in Surgery, 2025)
IntroductionPeri-lead edema (PLE) is a commonly observed but often asymptomatic complication of deep brain stimulation (DBS). While usually transient and benign, severe cases of PLE can result in neurological symptoms, impacting patient outcomes. This case series explores the clinical course, management, and outcomes of symptomatic PLE in a series of five patients undergoing DBS.ObjectiveTo analyze the presentation and management strategies for symptomatic peri-lead edema identified in patients undergoing DBS for movement disorders.MethodsA retrospective review of 191 patients who underwent DBS at the University Hospital in Olomouc, Czech Republic, between 2008 and 2024 was conducted. Postoperative imaging and clinical follow-ups were used to identify and evaluate cases of symptomatic PLE. Patients who developed symptomatic PLE were treated with corticosteroids and monitored through imaging and neurological assessments.ResultsAmong the 191 patients, we identified 5 (2.6%) who developed symptomatic PLE characterized by cognitive decline, motor disturbances, and, in some cases, pseudocyst formation. Symptoms typically presented several weeks to months postoperatively. Management with corticosteroid therapy resulted in clinical improvement and resolution of edema in all cases. Following the resolution of PLE, DBS therapy was successfully re-initiated, achieving favorable therapeutic outcomes.ConclusionsSymptomatic PLE is a rare but clinically significant complication of DBS. Early detection and timely management with corticosteroids are critical for symptom resolution and successful continuation of DBS therapy. Vigilant postoperative monitoring and further research are essential to improve understanding and management of PLE.